If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1x + -4 = 28 Reorder the terms: -4 + 1x = 28 Solving -4 + 1x = 28 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 1x = 28 + 4 Combine like terms: -4 + 4 = 0 0 + 1x = 28 + 4 1x = 28 + 4 Combine like terms: 28 + 4 = 32 1x = 32 Divide each side by '1'. x = 32 Simplifying x = 32
| x^2+x-36=0 | | 9r^2-5=607 | | 120=0.04v^2+1.1v | | 120=0.04v^2+1.1b | | 4c-1=8-2c | | 4+3(2r+2s)3r= | | x^2+x-18=0 | | 2x^2y-2xy-12y=0 | | -7(10r+3)+8(7r+8)= | | -7(d+7)=d+11+2d | | 3.8=n-3.62 | | x^3-3x^2-54x=0 | | 100*31=250xx | | 1.2y=4.8 | | -x^2-11x-30=0 | | 2x^2+24x+72=0 | | (3n-2)(4n+1)= | | 52=2(2x+5)+2x | | -18=-9t | | -2x^3+10x^2+28x=0 | | 4a+6-4a=10 | | x^4-16x^2-225=0 | | 4a+6-4a=-10 | | 16k=32 | | 3x^3-12x^2-96x=0 | | 6(x+3)=-2(x+31) | | 3(y)+6-10=89 | | 21=2[4x+2] | | x+3=x-15 | | (5x-1)(3x+4)=0 | | (5x-1)(34+4)=0 | | 3x^2+30x+48=0 |